A structural approach to integrating total quality management and knowledge management with supply chain learning - Loke, Siew-Phaik; G. Downe, Alan; Sambasivan, Murali; Khalid, Khalizani (Journal of Business Economics and Management, 2012)
The aim of this study is to integrate total quality management (TQM) and knowledge management (KM) into a unified framework to study supply chain learning among partnering firms. The impacts of TQM practices (e.g. leadership, strategic planning, customer focus, information analysis, people management and process management) and KM practices including KM process, leadership in KM, KM culture, KM technology and KM measurement on supply chain learning were examined. In this study, mail questionnaire have been sent to the managers consists of the Malaysian manufacturing and service firms. A total of 202 firms participated in this study. While greater level of TQM practices tends to enhance KM practices, we found that both TQM and KM are significantly positively related to supply chain learning. The findings of this study empirically tested and confirmed the proposed integrated model. It is hoped that findings from this paper can provide greater understanding in the areas of quality and knowledge management, and illustrate how these practices can enrich the supply chain learning among partnering firms.